Parental Risk for Suicide and Attachment Patterns Among Adolescents With Borderline Personality Disorder. A Clinical-Based Study - Moscoso, Ana; Speranza, Mario; Delvenne, Veronique; Corcos, Maurice; Pham-Scottez, Alexandra (Frontiers in Psychiatry, 2019)
INTRODUCTION: Experiencing adverse life events and early disturbed patterns of interaction are crucial determinants for the development of Borderline Personality Disorder (BPD). Parental suicidal attempts can be considered a major adverse life event and a potentially traumatic experience. The aim of this study was to examine differences in parental suicidal attempts among a BPD adolescent population vs. a matched control group. We also aimed to understand if attachment styles and the number of parental suicidal attempts predicted the severity of borderline symptomatology. METHODS: Our study (EURNET BPD) comprised 85 BPD adolescents and 85 matched controls. Axis II disorders were investigated using the French version of SIDP-IV. Parental suicidal behaviors were assessed during a face-to-face interview with the adolescent. Attachment style was assessed with the Relationship Questionnaire (RQ). RESULTS: Parents of BPD adolescents made more suicidal attempts than controls (34% vs. 11%; chi2 = 13.8, p<0.001). The linear regression showed that the best model explaining the severity of borderline symptomatology (R2adjusted = .15, F=4.65, p<0.001) was a model including the number of suicidal attempts realized by the parent (standardized beta = 0.28, p=0.009) and the preoccupied attachment style of the adolescents toward their parents (standardized beta = 0.21, p=0.043). CONCLUSION: Our results highlight the usefulness of assessing parental suicidal behaviour when interviewing patients with BPD traits. This could be useful in clinical practice as an early clue to identify patients with potentially severe clinical profiles and parents needing a specific support. Further research is needed to confirm our findings.